Evaluating Peer-Led Study Groups In Educational Psychology, Performance, And Student Perception In Smp Islam Kepenuhan Kota Tengah Rokan Hulu - Hayati, Najmi; Akzam, Ismail; Antoni Putra , Ary; Supriyady, Harif; Harahap, Musaddad; Syarif , Miftah; Astuti, Daharmi (CV. Pustaka An Nur, 2025)
This community service project aims to evaluate the impact of peer-led learning groups in secondary school educational psychology on students' academic performance and perceptions of collaborative learning. The project was implemented from October to December 2024 at SMP Islam Kepenuhan Kota Tengah, Rokan Hulu Regency, Riau Province. The implementation of this community service project followed a structured, step-by-step approach designed to address identified gaps and partner challenges. Participants of 60 students were divided into two groups: those who participated in peer-led learning groups (experimental group) were 30 students, and those who received traditional teacher-led instruction (control group) were 30 students. The findings revealed that students in peer-led learning groups showed an 18% higher increase in academic performance than the control group. Survey results showed a significant increase in positive perceptions of collaboration, with 87% of students reporting that peer-led discussions improved their understanding of the material. Challenges identified included uneven participation in some groups and the need for additional training for peer leaders to effectively manage group dynamics. Peer-led learning groups are a viable strategy for improving secondary school students’ academic performance and perceptions of collaborative learning. These results highlight the importance of empowering students to actively participate in their education. Future initiatives should focus on providing comprehensive training for peer leaders and addressing group management issues to maximize the effectiveness of this approach.